2023
DOI: 10.1007/jhep02(2023)027
|View full text |Cite
|
Sign up to set email alerts
|

Large N superconformal indices for 3d holographic SCFTs

Abstract: We study a limit of the superconformal index of the ABJM theory on S1 × S2 in which the size of the circle is much smaller than the radius of the two-sphere. We derive closed form expressions for the two leading terms in this Cardy-like limit which are valid to all orders in the 1/N expansion. These results are facilitated by a judicious rewriting of the superconformal index which establishes a connection with the Bethe Ansatz Equations that control the topologically twisted index. Using the same technique we … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 129 publications
1
3
0
Order By: Relevance
“…However, the generic form of other partition functions given in [2] still relies on the full validity of (4.1) combined with the gluing rules for the particular background in question. It is a non-trivial holographic check that both the twisted and the identity gluing rules (see [1,18]) lead to the correct finite N answer for the topologically twisted and superconformal indices of ABJM, respectively, as numerically verified in [61] and [62]. Additionally, at large N , the refined topologically twisted index of ABJM was also shown in [63] to agree with the proposed gluing rules applied to (4.1), generalizing the analytic result of [64].…”
Section: Jhep02(2023)110supporting
confidence: 66%
“…However, the generic form of other partition functions given in [2] still relies on the full validity of (4.1) combined with the gluing rules for the particular background in question. It is a non-trivial holographic check that both the twisted and the identity gluing rules (see [1,18]) lead to the correct finite N answer for the topologically twisted and superconformal indices of ABJM, respectively, as numerically verified in [61] and [62]. Additionally, at large N , the refined topologically twisted index of ABJM was also shown in [63] to agree with the proposed gluing rules applied to (4.1), generalizing the analytic result of [64].…”
Section: Jhep02(2023)110supporting
confidence: 66%
“…where the coefficients (α, B, C) are the same as the ones appearing in the topologically twisted index (4.4). We note that in [37] this relation between the two different indices was shown analytically for the N = 6 ABJM theory and the 3d N = 4 SYM theory known as ADHM (or the N f model). We have recently improved on this analysis and have shown that this relation is valid for general 3d N = 2 SCFTs [38] and we can therefore employ it safely in our current discussion.…”
Section: Jhep12(2023)054mentioning
confidence: 55%
“…The superconformal index can be studied in the Cardy-like limit of small ω, which physically corresponds to the limit where the size of the S 1 circle is much smaller than the radius of the S 2 . 7 In this regime, it was shown in [37] that the index takes the form…”
Section: Jhep12(2023)054mentioning
confidence: 99%
“…For a number of interesting theories, we have managed to obtain a perturbatively exact analytic answer for their TTI, which we will report on in a forthcoming publication [70]. Moreover, in [71] we will show how similar numerical techniques can also be leveraged to derive analytic answers for the superconformal index of 3d holographic SCFTs.…”
Section: Jhep02(2023)020mentioning
confidence: 97%